BP: serum anti‐BP180 IgG levels, mortality and Karnofsky score. (1st October 2018) - Holtsche, M.M.; Goletz, S.; van Beek, N.; Zillikens, D.; Benoit, S.; Harman, K.; Walton, S.; English, J.; Sticherling, M.; Chapman, A.; Levell, N.J.; Groves, R.; et al.
Summary: Bullous pemphigoid (BP) is a rare, chronic skin disease that causes blistering and severe itching, mainly in elderly patients. It is an autoimmune skin disease, in which the body's own immune system is directed against structures of the skin. Specific proteins, named autoantibodies, are produced and lead to inflammation. It affects about 259 per million people in Germany. In a recent published clinical trial, two different therapies for BP were compared in 253 BP patients in the U.K. and Germany. This additional study, again from Germany and the U.K., aimed to find out if there are any markers in the blood of these patients that tell us about the course of the disease. Therefore the authors investigated the blood of 143 patients taking part in a trial called the BLISTER trial. Several tests were performed to check for the amount of autoantibodies in the blood of these patients. Afterwards the results were linked with basic parameters including age, general condition, number of blisters, side effects, and mortality. The study revealed that patients with a poor general condition had higher levels of both specific autoantibodies which cause the disease. Patients who died within one year of inclusion to the study had higher amounts of one of the specific autoantibodies. The presence of the other specific autoantibody was more frequent in older patients. In conclusion, analyzing the autoantibody profile not only helps in diagnosis, but may also be helpful in predicting the course of the disease.